DUA ASPEK DIMENSI LOYALITAS - Budi Budi (Universitas Bunda Mulia, 2017)
We live in hyper-competitive era. Thousands of new products have been launched every year. Consumers have abundant choice of products to meet their needs. In this condition, loyalty considered much more important than before. In order to survive, companies are in race to win consumer loyalty. Consumer loyalty has two dimensional aspects which attitudinal loyalty and behavioural loyalty. Attitudinal loyalty tends to higher relative brand pricing. While, behavioural attitudinal will tend to higher share market. Key Words-Loyalty, Behavioral Loyalty, Loyalty Factors, Satisfaction